Diagnosing the plasma formed during acoustic cavitation in [BEPip][NTf2] ionic liquid. Issue 3 (14th December 2018) - Pflieger, Rachel; Lejeune, Manuel; Noel, Cédric; Belmonte, Thierry; Nikitenko, Sergey I.; Draye, Micheline
Abstract : What do rovibronic temperatures tell us? Example of the sonolysis of [BePip][NTf2 ] ionic liquid. Abstract : Sonoluminescence (SL) spectra of a very dry [BEPip][NTf2 ] ionic liquid were measured in the first minutes of sonication under Ar. The intense sonoluminescence allowed us to monitor the time-evolution of the SL spectra. Several molecular emissions were observed. Rovibronic temperatures of C2 and CN were determined giving vibrational temperatures of 5800 ± 500 K and 6000 ± 500 K and rotational temperatures ( i.e. translational or gas temperatures) of 4000 ± 500 K. These temperatures stay remarkably constant during the sonolysis, while SL spectra undergo strong changes that illustrate the very fast evolution of the plasma during the first minutes of sonication. The expected strong decrease in the plasma electron energy also reflects in the evolution of the populations of CH electronically excited states. The physical meaning of temperatures derived from molecular emissions in SL spectra is discussed.